1988
DOI: 10.1038/jcbfm.1988.144
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Concentrations of ATP, Phosphocreatine, Lactate, and Tissue pH in Relation to Reduced Cerebral Blood Flow following Experimental Acute Middle Cerebral Artery Occlusion

Abstract: Local CBF (LCBF) was compared with the corresponding local tissue concentration of ATP, phosphocreatine (PCr), and lactate in anaesthetized baboons subjected to focal ischaemia produced by middle cerebral artery occlusion (MCAO). LCBF hydrogen electrodes were implanted in cortical regions where MCAO had been previously shown to produce severe and penumbral ischaemia and in posterior regions where blood flow is not altered. Metabolites were assayed in small tissue samples collected either by cryoprobe biopsy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 31 publications
(16 reference statements)
2
30
0
Order By: Relevance
“…Lactate and arachidonic acid, which are released by ischemia, might also enhance ASIC activity (13,42,43). An ASIC1-mediated increase in Ca 2ϩ influx could contribute to Ca 2ϩ overload, an important mechanism of cell damage and death in ischemia (37).…”
Section: Discussionmentioning
confidence: 99%
“…Lactate and arachidonic acid, which are released by ischemia, might also enhance ASIC activity (13,42,43). An ASIC1-mediated increase in Ca 2ϩ influx could contribute to Ca 2ϩ overload, an important mechanism of cell damage and death in ischemia (37).…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting the mouse ASIC1 gene markedly reduced H ϩ -gated currents in hippocampal neurons, impaired long-term potentiation of synaptic transmission, and produced learning and memory deficits (11). The observation that extracellular acidosis activates ASIC1 has suggested that it may also be activated in pathologic conditions, for example, when extracellular pH falls during cerebral ischemia (12,13). Because protein kinases regulate the function of many brain ion channels, we asked whether ASIC channels are phosphorylated.…”
mentioning
confidence: 99%
“…In an in vitro study, 2DG suppression of synaptic transmission in the CA1 region of hippocampal slices was observed (Tekkok and Krnjevic, 1995). These data suggest that inhibiting energy-dependent processes can reduce hypermetabolic neuronal necrosis, which involves ATP depletion and lactate accumulation (Obrenovitch et al, 1988), glutamate excitotoxicity, and increased free radical formation. Here we test the hypothesis that by manipulating neuronal stores of glucose we can affect intracellular formation of lactate, thereby preventing the exacerbation of the brain lesion volume resulting from MCAO/R.…”
mentioning
confidence: 87%